Servant and Spiritual Leadership Theories: Are They Two Different Notions? (2016)
The aim of this study is to analyze if two emergent models of leadership, servant and spiritual are really different or, on the contrary, are similar, with different labels. Both approaches were analyzed from their backgrounds, depictions, definitions, theoretical models proposed and limitations. It is concluded that both models of leadership are about the same models that share a similar root; both of them are oriented towards transcendental values of employees as a core component of leadership and a main factor related to the quality of job performance. Further studies should be done in order to provide new empirical evidence to support whether servant and spiritual leadership can be considered as completely independent models. © SAGE Publications.